2003
DOI: 10.1002/jemt.10257
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis of non–small cell lung cancer

Abstract: Lung cancer is one of the commonest causes of cancer death in developed countries. Recent evidence suggests that angoigenesis is related to poor prognosis in many solid tumors including non-small cell lung cancer (NSCLC). Angiogenesis is regulated by a complex interaction among growth factors and cytokines and influenced by proteolytic enzymes such as plasminogen activators and matrix metalloproteases, expression of adhesion molecules, and distribution of extracellular matrices. Fibroblasts, macrophages, mast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 202 publications
(215 reference statements)
1
33
0
Order By: Relevance
“…Our previous observations have demonstrated that microvessel and mast cell densities in lung adenocarcinomas were significantly greater than those in lung squamous cell carcinomas and that microvessel and mast cell densities were closely asso- ciated with tumor-cell VEGF in lung adenocarcinomas. 29,33,34 The different functions of VEGF and VEGF-C in relation to tumor histology may reflect clinical behaviors of lung adenocarcinomas and squamous cell carcinomas. Tumor-cell VEGF-C in lung adenocarcinomas and squamous cell carcinomas should be clarified in large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous observations have demonstrated that microvessel and mast cell densities in lung adenocarcinomas were significantly greater than those in lung squamous cell carcinomas and that microvessel and mast cell densities were closely asso- ciated with tumor-cell VEGF in lung adenocarcinomas. 29,33,34 The different functions of VEGF and VEGF-C in relation to tumor histology may reflect clinical behaviors of lung adenocarcinomas and squamous cell carcinomas. Tumor-cell VEGF-C in lung adenocarcinomas and squamous cell carcinomas should be clarified in large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…An infiltration of mast cells has been found in a variety of human cancers, including non-small-cell lung cancer (Shijubo et al, 2003), breast cancer (Kankkunen et al, 1997), colorectal cancer (Lachter et al, 1995), basal cell carcinoma (Yamamoto et al, 1997) and pulmonary adenocarcinoma (Imada et al, 2000). The accumulation of mast cells has been associated with enhanced growth and invasion of several human cancers (Ribatti et al, 2001).…”
Section: Mast Cellsmentioning
confidence: 99%
“…OPN is an important adhesive bone matrix protein and plays a key role in immune cell recruitment, wound healing and tissue remodeling (5). OPN contains 314 amino acids with extensive post-translational modifications, including phosphorylation and N-linked glycosylation, which result in electrophoretic mobility between 44 and 75 kDa.…”
Section: Introductionmentioning
confidence: 99%